ELECTRONIC LEARNING FOR EDUCATIONAL SUSTAINABILITY IN THE PANDEMIC ERA: A CRITICAL REVIEW - HADI BUHARI SHUAYAU; HUSSAINI IBRAHIM SULE (International Studies Journal)
Education is one of the key aspects of states’ economies around the world, and it has served as the foundation for all significant achievements in any country.Since it has been established that the sustainability of the education sector is critical to the development of any nations’ economy and all round development, no nation conscious of development can therefore allow her educational system to be paralyzed or shut down for any reason. Therefore, the viability of the education sector of any nation must be sustained irrespective of any threatening factor that may be confronting the nation. It is worth noting that electronic learning, often known as virtual or e-learning, was previously neglected, particularly in underdeveloped nations. However, because of the outbreak of the COVID-19 pandemic, the whole world is obliged to resort to virtual learning for educational purposes. Most countries throughout the world were forced to impose a non-negotiable lockdown on all sectors, including education, as a result of this pandemic.virtual learning was also imperative in order to ensure the sustainability of academic work at the national level in every country across the world. Since its introduction, electronic learning has risen to prominence and came to the rescue of education sectors in the face of the ravaging pandemic.Be that as it may, many other institutions were unable to do so in view of some circumstances beyond their control. This pandemic however brought to the fore, the unreadiness or unpreparedness for virtual learning.The aim of the project is to examine the adoption and usage of electronic learning for educational sustainability in the pandemic era.This study took the form of a review of relevant literature. The review collected and summarized qualitative data connected to keywords that are closely related to the four research questions that have already been proposed to lead the research.